The Use of Biofilm Biofertilizer to Increase Smart Farming System in Mustard Yield and Improve Soil Physical Properties of Vertisols - Sudadi, Sudadi (Journal of Smart Agriculture and Environmental Technology, 2024)
Soil serves as the growing medium and source of nutrients for plants. Vertisol soil, however, does bring with it some flaws particularly its physical characteristics. The application of organic fertilizer decomposed with Biofilm biofertilizer, thus, isexpected to improve the physical characteristics of soil and yield of mustard. The aim of the research is to study the effect of the dose of organic fertilizer decomposed by Biofilm biofertilizer to the betterment of Vertisol soil physical characteristics and the mustard yield. The experiment was completed in a field with Randomized Complete Block Design consisting of a single treatment factor in the form of Biofilm biofertilizer. The data obtained from the series of observations was analyzed based on the F test with 95% confidence level followed by Duncan’s Multiple Range Test (DMRT). The variables of the observations involve the mustard plant yield and the soil physical characteristics. The study shows that the application of the organic fertilizer decomposed by Biofilm bio-fertilizer provides significant effects towards the improvement of the vertisol soil’s physical characteristics and the increase in mustard plant yield. The dose 21 tons/ha results in the highest increase in the mustard plant production and the best improvement of the vertisol soil physical characteristics. Organic fertilizer decomposed by Biofilm bio-fertilizer 21 tons/ha helps in developing permeability as much as 685.71%; aggregate stability index 201.6%; organic material 20.74%; and porosity 122.38%. Also, organic fertilizer decomposed by Biofilm bio-fertilizer 21 tons/ha can boost the mustard plant production as much as 4.25 tons/ha compared to the absence of organic fertilizer decomposed by Biofilm bio-fertilizer.